Children's Response towards Extensive Reading - Hermini Hermini (Institut Agama Islam Negeri Palopo, 2021)
The research aimed to find the children’s responses toward Extensive Reading. It is quantitative research. The sample was six children of an elementary schools around literacy corner which taken by random sampling. The instrument was questionnaire. The result shows that the children’ responses toward extensive reading was 88.5 which was categorized into positive. The children’s responses are mostly positive based on characters of extensive reading but it does not fit to goal of reading and linguistic competence. The responses toward goal of reading related to searching new information was 67 which is categorized into less positive and their responses toward linguistic competence related to finding new vocabulary was 50 which was categorized into negative. Children read for enjoyment so they do not focus on linguistic competence related to gaining new vocabulary and goals of reading related to searching new information. As conclusion, the children’s responses toward extensive reading was positive and practice guide of reading and teacher’s assistance are needed in promoting extensive reading for children to build reading habit.